Pemahaman Perawat terhadap Supervisi Klinis Berjenjang di Ruang Rawat Inap Rumah Sakit Umum ‘Aisyiyah Padang: Nurses' Understanding of Tiered Clinical Supervision in the Inpatient Room of 'Aisyiyah General Hospital Padang - Silvi Korprina; Husna Yetti; Rika Sarfika (Fakultas Keperawatan Universitas Andalas, 2024)
The effectiveness of implementing tiered clinical supervision has a significant impact on improving nurses’ competency in nursing care delivery while also enhancing the safety and quality of care. This study aimed to explore nurses’ comprehension of tiered clinical supervision in optimizing the effective implementation of tiered clinical supervision at RSU 'Aisyiyah Padang. This study used a qualitative method with a phenomenological approach. Data collection was conducted through observation, document analysis, and in-depth, semi-structured interviews with 11 participants, namely nursing associates and three levels of nursing managers in the inpatient room. The interview data were transcribed, edited, coded, and analyzed thematically. The results showed that the understanding of 1) An insufficiently precise description in defining clinical supervision, with no evaluation element of this definition; 2) Supervision is considered to be best practice for all staff nurses both for new (novice) and senior (expert) nurses; 3) For nurses, the objectives and benefits of tiered clinical supervision include improving understanding, competence, skills, as well as confidence and self-assurance, thus preventing practice errors (malpractice). Also for patients, this clinical supervision has a significant benefit in patient safety improvement. It is important to provide training or educate staff related to tiered clinical supervision to enhance comprehension, in optimizing the effective implementation of tiered clinical supervision.